The complete chloroplast genome of Carpinus hebestroma, a critically endangered species endemic to Taiwan - Gaini Wang; Ying Li (Mitochondrial DNA. Part B. Resources, 2018)
Carpinus hebestroma (Betulaceae) is a critically endangered species endemic to Taiwan. In this study, we assembled the complete chloroplast (cp) genome of C. hebestroma and the cp genome was 159,231 bp in length, including a large single copy (LSC) region of 88,168 bp, a small single copy (SSC) region of 18,874 bp and a pair of inverted repeats (IRs) of 52,189 bp. The genome contained 124 genes, including 85 protein-coding genes, 30 tRNA genes and 8 rRNA genes. The overall GC content of the chloroplast genome was 36.46%. A phylogenetic analysis demonstrated a close relationship between C. hebestroma and Ostrya rehderiana.